OBSTACLES TO THE USE OF ELECTRONIC MARKETING IN MARKETING IRAQI INSURANCE POLICIES: APPLIED STUDY IN A NUMBER OF IRAQI INSURANCE COMPANIES (World Bulletin of Management and Law, 2022)
The advent of the Internet has enabled the introduction of new financial products and services in different packages and has also fundamentally changed the business environment by reaching anyone. Geographical distance is no longer limited. A new method of marketing services based primarily on information technologies, called e-marketing or e-commerce, has emerged in the past years and has been a major challenge in the activities of organizations and has begun to rely on it to make clear progress and outperform their competitors, leading all organizations to seriously consider developing Marketing its services to keep abreast of these developments. In the Internet age, companies can interact directly with market changes in a few minutes, and this forced Iraqi insurance companies to adopt a flexible marketing strategy to react quickly to these bullies in the business environment because the Iraqi insurance service differs from the other intangible services that surround Iraqi society This is due to the lack of security awareness on the one hand and the developments the world has witnessed in recent years in the field of communications technology on the other hand. The main purpose of the current study is to uncover the effect of the obstacles to the use of electronic marketing in marketing Iraqi insurance policies. The study concluded that the new challenge facing Iraqi insurance companies requires changing from the traditional methods in their dealings with individuals to the new advanced and fast-growing methods, and the results also showed that all variables in the study have an effect on limiting the use of electronic marketing in Iraqi insurance companies This kind of service is of a special nature that differs from the marketing of the rest of the services because there are many factors, including insurance companies themselves and the Iraqi individual. It also referred to the necessity of spreading insurance awareness inside the Iraqi society and its importance in reducing risks in an environment where danger is most prevalent due to the circumstances Iraq is going through and increasing electronic awareness on the other hand in order to achieve the success of marketing insurance trust in Iraq